P266 Early lung cancer team intervention in emergency admissions. (15th November 2017) - Dunbar, J; Walshaw, M; Ledson, M; McIver, A; Hughes, J; Maddock, N; Smyth, C
Abstract : Introduction: Although the majority of cases of suspected lung cancer can be managed as outpatients where the diagnostic pathway is well developed, a proportion still present unwell via the emergency department where their subsequent journey is less certain. Along with same-day reporting for emergency scans, we have developed a rapid review service for such individuals and were interested in assessing its performance. Methods: We looked at all patients with suspected lung cancer who presented through our emergency department for the first 6 months of 2017, focussing on outcome, time to be seen following admission, and the histological diagnosis rate. Results: Of the 285 referrals to our lung cancer unit, 85 (32%) presented through the emergency department: 21 (25%) of these were discharged to outpatient cancer investigation. The remaining 64 (75%) were subsequently admitted to 29 different locations (8 medical specialities, surgical, vascular and orthopaedic wards). Of these, 55 (86%) were seen by the lung CNS within one working day and an appropriate management plan initiated. This was aided by our live CT database, where 50 suspicious scans were coded the same day enabling early review by the lung clinician and CNS, often before formal referral from the responsible clinical team was made. Overall 70 patients (82%) who presented as emergencies subsequently were diagnosed with a malignancy, and of these 34 (49%) had histological confirmation. Conclusions: Our Results show that, by coordinating care between the emergency and radiology departments and the lung cancer team, patients presenting unwell can be managed rapidly even if they remain in hospital. In addition, by actively seeking them out we can not only provide them with timely and appropriate investigations but also early CNS intervention, facilitating symptom management and psychological support.